ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, TIPE INDUSTRI, PERTUMBUHAN PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013-20 - Nita Rizky Berlianti, 15.05.52.0255; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2019)
The purpose ot this study was to analyze the effect of profitability, leverage, firm size, industry type, company growth and environmental performance on disclosure of Corporate Social Responsibility (CSR). In this study the population used is manufacturing companies listed on the Indonesia Stock Exchange during the period 2013-2017. Sampling using purposive sampling method, namely manufacturing companies during 2013-2017, which amounted to 701 companies that fit the criteria. Data testing technique is to use multiple linier regression analysis. The results of the study show that the variable that has a significant positive influence on disclosure of Corporate Social Responsibility (CSR) is the profitability and growth of the company. Whereas Leverage and environmental performance negatively affect disclosure of Corporate Social Responsibility (CSR). Then for company size and industry type variables do not affect the disclosure of Corporate Social Responsibility (CSR).